(untitled) (Journal of Management and Social Sciences, 2025)
This study investigates how multinational corporations (MNCs) in Nigeria contribute to achieving Sustainable Development Goals (SDGs) through sustainable finance and corporate governance practices. Employing a quantitative research design, secondary data from ten listed MNCs in Nigeria between 2015 and 2024 were analyzed. Panel regression models, descriptive statistics, and correlation analysis were used to test the relationship between sustainable finance, corporate governance, and SDGs. The study’s results reveal that sustainable finance positively influences investment in eco-friendly projects, while effective corporate governance fosters accountability. Executive compensation linked to sustainability metrics promotes SDG alignment. This study concludes that sustainable finance and corporate governance play critical roles in advancing SDG objectives in Nigerian MNCs. Sustainable finance practices, particularly investments in green projects, contribute to long-term environmental and economic stability. Strengthening corporate governance mechanisms including board oversight and ethical financial reporting practices is essential to fostering SDG-aligned growth. Firms’ managers should integrate digital accounting tools and align executive incentives with SDG objectives. This study provides empirical insights into how sustainable finance and corporate governance drive SDG achievement in an emerging economy, bridging knowledge gaps in Nigeria’s context. Keywords Corporate governance, sustainable finance, SDGs, Nigerian multinational corporations